TRENDS OF PLACING PRODUCT ADVERTISEMENTS ON ENTERTAINMENT AND INFORMATION SHOWING ON NATIONAL BROADCASTING TELEVISION - Ine Anggraini; Jan Jan Eka Sulistiana; Monique Dzulfairda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Television is the most effective place in the world of advertising. Many formats or forms are currently developing in television shows, creating a new phenomenon about the number of advertisements that are made by advertisers in informative and entertainment television shows. The purpose of this study was to determine what kind of product advertisement placement advertisers tend to choose on entertainment programs on national broadcast television and what kind of product advertisement placements advertisers tend to choose on informative programs on national broadcast television. The method used in this research is content analysis . The instrument used is a coding sheet format with six product placement indicators , namely visual dimension, auditory dimension, plot connection dimension (PCD), implicit product placement, integrated explicit product placement, non-integrated explicit product placement . The results showed that in the iNews afternoon news program, there were three types of product placement integration that were chosen by advertisers and creative teams into their advertisements, namely visual dimensioning, Implicit product placement and Non-Integrated explicit product placement techniques. While in the soap opera Bond of Love, there are four types of placement product integration that are most chosen by advertisers and creative teams into their advertisements , namely visual dimensioning techniques, Auditory dimensions, Plot connection dimensions (PCD) and Non-Integrated explicit products. placements.